The mechanics of the squash nick shot - Mithun Ravisankar; Madeline E. Federle; Mina Bahadori; Asimanshu Das; Haneesh Kesari; Roberto Zenit (Proceedings of the National Academy of Sciences, 2025)
Squash is a widely popular racket sport, practiced by millions of people worldwide, played inside a walled court. When played well, players can last for several minutes before the ball bounces twice on the floor. There is, however, an unanswerable shot. When the ball hits the nick between a vertical wall and the floor, under certain conditions, it rolls without any vertical bounce. We study this process experimentally. We determined that the ball must hit the vertical wall first at a narrow range of heights above the floor, but most importantly, it must touch the floor before finishing its rolling time on the vertical wall. When the rolling time is shorter than the contact time, the vertical momentum is canceled due to a mechanical frustration condition. This behavior is explained considering a contact model, which agrees with the experimental observations. In addition to its relevance to other walled ball sports, this understanding could help design rolling shock dampers with possible practical applications.